Dimensi Religiusitas Agensi Pendidikan Politik Partai NasDem Jawa Timur - Luluk Mashluchah (Postgraduate Studies of Universitas Islam Negeri Sunan Ampel Surabaya, Indonesia, 2020)
Religious discourse in political praxis always attracts the attention of many experts. Some of them consider that the use of religion represents more pragmatic interest of political parties for stimulating voters in general elections. This study argues that the use of religion in political praxis is not merely for the pragmatic purposes of the party, but also for the party’s idealistic goals. This is the reason that makes the implementation of political education important for integrating religious dimensions. NasDem Party of East Java is known for its concern in promoting its ideal image as a nationalist-religious party. In order to realize its image and political vision, NasDem carries religion-based politics in its political education. This article aims to study issues such as how religious dimensions are contained in political education and how the orientations of the agency of political party are. This article found an important finding that there were two dimensions in the implementation of political education, namely the ritual-symbolic and substantive religious dimensions. The orientation of the symbolic religious dimension is to strengthen the faith and the creation of nationality-religious integrated understanding, while the substantive dimension is oriented to shape a humanist-religious consciousness and God’s mandate in the political role.